2007
DOI: 10.1093/ajcn/85.3.887
|View full text |Cite
|
Sign up to set email alerts
|

Zinc during and in convalescence from diarrhea has no demonstrable effect on subsequent morbidity and anthropometric status among infants <6 mo of age

Abstract: Young infants do not appear to benefit from 2 wk of zinc, unlike what has been observed among older children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 26 publications
1
43
0
Order By: Relevance
“…Similarly, a study in Delhi, India, involving infants 6-11 mo of age, reported that a short course of daily zinc supplementation for 2 wk effectively reduced the subsequent number and duration of diarrhea episodes (20). In contrast, a multicenter study involving infants 1-5 mo of age with acute diarrhea found that infants who received therapeutic zinc supplementation for 14 d had more days of diarrhea and similar prevalence of pneumonia and respiratory infection compared with the placebo group (21). Differences in the age of study participants, dose and duration of supplementation, and length of follow-up make it difficult to identify the reasons behind these contrasting results.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study in Delhi, India, involving infants 6-11 mo of age, reported that a short course of daily zinc supplementation for 2 wk effectively reduced the subsequent number and duration of diarrhea episodes (20). In contrast, a multicenter study involving infants 1-5 mo of age with acute diarrhea found that infants who received therapeutic zinc supplementation for 14 d had more days of diarrhea and similar prevalence of pneumonia and respiratory infection compared with the placebo group (21). Differences in the age of study participants, dose and duration of supplementation, and length of follow-up make it difficult to identify the reasons behind these contrasting results.…”
Section: Discussionmentioning
confidence: 99%
“…24 It should be noted, however, that a study of the effect of treatment with zinc for diarrhoea in infants < 6 months old on subsequent diarrhoeal and respiratory morbidity failed to document any benefit. 25 A subgroup analysis of a trial in Bangladesh 24 also suggested that zinc reduced the duration of diarrhoea and subsequent morbidity and mortality in infants < 6 months of age, although the sample sizes were small in the age-stratified subgroups. 26 We defined ALRI as a caregiver's report of the presence of cough or difficulty in breathing along with rapid breathing.…”
Section: Discussionmentioning
confidence: 99%
“…Seven (5%) of the studies operationalized diarrhea on the basis of the mother's perception. [15][16][17][18][19][20][21] One hundred three studies (75%) provided a definition of diarrhea resolution (offset), 69 (50%) of which provided a unique description of resolution. Of the 70 unique definitions, 27 provided Ն3 criteria (frequency, consistency, duration), 18 provided 2 criteria, and 24 provided 1 criterion.…”
Section: Definitions Of Diarrhea and Its Resolutionmentioning
confidence: 99%